Disability, Reasonable Accommodation and the Employer's Obligations: Nano Nagle School v Daly. Issue 5 (3rd June 2020) - Ryan, Desmond; Bell, Mark
Abstract: The duty on employers to provide reasonable accommodation is a well‐established component of disability discrimination legislation, yet it continues to generate litigation in many jurisdictions. This article examines a recent decision of the Irish Supreme Court concerning the extent of the employer's obligations where, after having acquired an impairment, a worker is no longer able to perform all of the functions of her original job. The case also addressed the question of what procedures should be followed by an employer when considering the provision of reasonable accommodation, as well as the need for courts to justify awards of compensation. The issues in Irish law were intertwined with obligations arising from EU and international law instruments. Therefore, the decision is pertinent for other jurisdictions confronting similar challenges.